Growth‐dependent heterogeneity in the DNA damage response in Escherichia coli - Sebastián Jaramillo‐Riveri; James Broughton; Alexander McVey; Teuta Pilizota; Matthew Scott; Meriem El Karoui (Molecular Systems Biology)
Abstract In natural environments, bacteria are frequently exposed to sub‐lethal levels of DNA damage, which leads to the induction of a stress response (the SOS response in Escherichia coli). Natural environments also vary in nutrient availability, resulting in distinct physiological changes in bacteria, which may have direct implications on their capacity to repair their chromosomes. Here, we evaluated the impact of varying the nutrient availability on the expression of the SOS response induced by chronic sub‐lethal DNA damage in E. coli. We found heterogeneous expression of the SOS regulon at the single‐cell level in all growth conditions. Surprisingly, we observed a larger fraction of high SOS‐induced cells in slow growth as compared with fast growth, despite a higher rate of SOS induction in fast growth. The result can be explained by the dynamic balance between the rate of SOS induction and the division rates of cells exposed to DNA damage. Taken together, our data illustrate how cell division and physiology come together to produce growth‐dependent heterogeneity in the DNA damage response.